Do women who intermittently attend breast screening differ from those who attend every invitation and those who never attend?. (June 2014) - Coyle, C; Kinnear, H; Rosato, M; Mairs, A; Hall, C; O'Reilly, D
Objectives: Analysis of screening uptake usually dichotomizes women into attenders and non-attenders, though many women respond positively to some but not all invitations. This paper studies these intermittent attenders. Methods: A cohort of 8, 571 women invited for consecutive breast screens in the Northern Ireland Breast Screening Programme were followed in a study linking screening and census records. Multivariate logistic analysis was used to analyze the characteristics of those who attended both times (consistent), once (intermittent or 'one-time only'), or not at all (non-attenders). Results: Overall, 15.5% of women attended once and 13.4% were non-attenders. Non-attenders were characteristically disadvantaged (as measured by social renting, car access, and employment status), less likely to be married, and more likely to be healthy. One-time attenders were younger, and suffering poor health, though there was no association with either social renting or employment status. Privately rented accommodation and city living was associated with both one-time attendance and non-attendance. Conclusions: One-time attenders are an important and distinct subgroup of screening invitees in this analysis. Their distinct characteristics suggest that transitory factors, such as change in marital status, ill-health, or addressing difficulties through change of residence are important. These distinct characteristics suggest the need for different approaches to increase attendance, among both intermittent attenders and those not attending at all.